2015
DOI: 10.1590/1807-3107bor-2015.vol29.0030
|View full text |Cite
|
Sign up to set email alerts
|

Addition of mechanically processed cellulosic fibers to ionomer cement: mechanical properties

Abstract: In this study, conventional restorative glass ionomer cement (GIC) was modified by embedding it with mechanically processed cellulose fibers. Two concentrations of fibers were weighed and agglutinated into the GIC during manipulation, yielding Experimental Groups 2 (G2; 3.62 wt% of fibers) and 3 (G3; 7.24 wt% of fibers), which were compared against a control group containing no fibers (G1). The compressive strengths and elastic modulus of the three groups, and their diametral tensile strengths and stiffness, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…In general, our results are in agreement with previous laboratory studies by Silva et al ., who showed that addition of cellulose fibers (average length 1 mm) resulted in improved mechanical properties for conventional GICs . However, in contrast to our results, they reported that the compressive strength values of fiber‐reinforced GIC were almost double those of their unmodified GIC.…”
Section: Discussioncontrasting
confidence: 99%
“…In general, our results are in agreement with previous laboratory studies by Silva et al ., who showed that addition of cellulose fibers (average length 1 mm) resulted in improved mechanical properties for conventional GICs . However, in contrast to our results, they reported that the compressive strength values of fiber‐reinforced GIC were almost double those of their unmodified GIC.…”
Section: Discussioncontrasting
confidence: 99%
“…This material has been widely used as different types of scaffolds in tissue engineering owing to its toughness, minimal cell flattening, and high rigidity 28) . Silva et al 29,30) demonstrated that nano-cellulose fibers could enhance the mechanical properties of GIC due to their high specific area as well as the strong hydrogen bonds in their web-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we selected HAp200, which has a typical hexagonal crystal shape. In addition, some researchers have reported that cellulosic fibers improve the mechanical properties of GIC, including its compressive or diametrical tensile strength [28,29]. In our study, celluloses having either porous or spherical characteristics, UF-711 and CP-203, were also compared with HApS.…”
Section: Discussionmentioning
confidence: 95%